Severe Acute Respiratory Syndrome- Coronavirus 2 - Sjogren, Maria H. (2021)
The pandemic caused by SARS-CoV-2 in 2020 and still raging in 2021 is a global emergency where no country was spared from its high morbidity and mortality. Life changed in innumerable ways, from lock downs to job losses, isolation and mental health crisis. All countries suffered. If it were not for the quick development of medications and vaccines, coupled with preventive measures like facial masks, social distancing and frequent washing of hands, we will be in a worse chaos. Some countries like India and many in Latin America have been devastated and its consequences will be long felt even after the pandemic is controlled. Understanding the cause, its epidemiology and controlled measures is important. Although it took 100 years to encounter a global pandemic of this magnitude, scientists warn of almost inevitable future global pandemics. This review will explore some salient aspects of SARS-CoV-2 impact and measures to control the infection. The world’s death toll caused by SARS-CoV-2 exceeds 3 million and close to 200 million people have been infected. The available vaccines used in more than 400 million individuals, still fall short of producing herd immunity despite the high efficacy rate of most of them. There is a pressing need to immunize 80% or more. Some side effects to vaccine were reported, the majority of minor impact, although some rare ones are more serious such as thrombotic thrombocytopenia or myocarditis. Still the protection afforded from the vaccine vastly outweighs the risks and its wide use is encouraged.